Synthesis and antiviral evaluation of fluorinated acyclo-nucleosides and their phosphoramidates. (2nd January 2017) - Mahmoud, Sawsan; Li, Hao; McBrayer, Tamara R.; Bassit, Leda; Hammad, Sherif F.; Coats, Steven J.; Amblard, Franck; Schinazi, Raymond F.
ABSTRACT: A novel series of tetrafluoro and hexafluoro acyclic nucleosides and their phosphoramidates were successfully prepared from commercially available 2, 2, 3, 3-tetrafluoro-1, 4-butanediol and 2, 2, 3, 3, 4, 4-hexafluoro-1, 5-pentanediol in four to six steps. Their ability to block HIV, HCV, HSV-1, and HBV replication along with their cytotoxicity toward HepG2, human lymphocyte, CEM, and Vero cells was assessed.